Analysis Of the Influence of Work Discipline and Management Information System Information System on Employee Performance with Motivation as An Intervening Variable in The Employment BPJS Branch in Medan Raya - Damseria Magdalena Togatorop; M. Isa Indrawan (Lead Journal of Economy and Administration, 2024)
In this study, researchers wanted to see the direct and indirect effects between work discipline variables and management information systems as independent variables and motivation as an intervening variable and employee performance as the dependent variable. This type of research uses quantitative, this research was conducted at BPJS Employment Branch Office Se-Medan Raya. The population of this study was 80 employees and the sample used was all the population using the saturated sample technique. The data source used is primary data sources and the data collection carried out is to distribute questionnaires. The research model used is phat analysis with smart PLS version 3.3.3. as a research measurement tool. The results of this study are as follows: Work discipline has a positive and significant effect on employee performance with an original sample value of 1.246 and P values of 0.000. Work discipline has a positive and insignificant effect on motivation with an original sample value of 0.247 and p values of 0.074. Motivation has a positive and significant effect on employee performance with an original sample value of 0.278 and p values of 0.000. Management information system has a negative and significant effect on employee performance with an original sample value of -0.599 and p values of 0.009. Management information system has a positive and significant effect on motivation with an original sample value of 0.403 and p values of 0.012. Work Discipline has a positive and insignificant effect on employee performance through motivation indirectly with original sample results of 0.069 and p values of 0.104. Information Management System has a positive and significant effect on employee performance through motivation with an original sample value of 0.111 and p values of 0.022.